2020
DOI: 10.3897/mycokeys.66.50946
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new species of the Hypoxylon rubiginosum complex from Iran and antagonistic activities of Hypoxylon spp. against the Ash Dieback pathogen, Hymenoscyphus fraxineus, in dual culture

Abstract: During a survey of xylarialean fungi in Northern Iran, several specimens that showed affinities to the Hypoxylon rubiginosum complex were collected and cultured. A comparison of their morphological characters, combined with a chemotaxonomic study based on high performance liquid chromatography, coupled with diode array detection and mass spectrometry (HPLC-DAD/MS) and a multi-locus phylogeny based on ITS, LSU, rbp2 and tub2 DNA sequences, revealed a new species here described as Hypoxylon guilanense. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Furthermore, one non-supported clade containing H. fragiforme and allies (Hx3) was placed as sister group next to a clade containing mostly other genera like Pyrenopolyporus (P, 100% support), Daldinia and allies (99%/100%; E, D, R, T), Hypomontagnella (Hy, 100%) and other nested sequences with non- or low supported positions of Hypoxylon and Entonaema (E, Hx4, Hx5, Hx6) with moderate BS and high likelihood-ratio support (95%/58%). These patterns were already described by Wendt et al [ 2 ], Sir et al [ 20 ], and Pourmoghaddam et al [ 39 ]. The H. invadens -derived sequences were placed next to H. trugodes with maximum support (Hx5).…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, one non-supported clade containing H. fragiforme and allies (Hx3) was placed as sister group next to a clade containing mostly other genera like Pyrenopolyporus (P, 100% support), Daldinia and allies (99%/100%; E, D, R, T), Hypomontagnella (Hy, 100%) and other nested sequences with non- or low supported positions of Hypoxylon and Entonaema (E, Hx4, Hx5, Hx6) with moderate BS and high likelihood-ratio support (95%/58%). These patterns were already described by Wendt et al [ 2 ], Sir et al [ 20 ], and Pourmoghaddam et al [ 39 ]. The H. invadens -derived sequences were placed next to H. trugodes with maximum support (Hx5).…”
Section: Resultssupporting
confidence: 75%
“…Morphological analyses of microscopic characters were carried out as described by Pourmoghaddam et al [ 21 ]. Pigment colors were determined as described in the latter monograph, with colour codes following Rayner [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Stromata from Hypoxylon specimens were extracted using acetone as described previously [ 23 ] and subsequently analysed by high-performance liquid chromatography coupled to a diode array and electrospray mass spectrometric detection system (HPLC/DAD-ESIMS) with instrument settings as described recently [ 21 ]. Resulting UV/Vis and mass spectrometric data were compared with internal databases, comprising standards of known Hypoxylaceae and literature data [ 10 , 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytes belonging to the genus Hypoxylon and its associated asexual stage Nodulisporium have also been repeatedly reported to produce biologically active volatiles [121,122], even though the taxonomy of most of these strains and the identity of many of the volatile antibiotics produced by these fungi remain to be settled. Recently, an endophytic isolate that was unambiguously identified as H. rubiginosum was found to possess striking activities in dual culture against the Ash dieback pathogen, Hymenoscyphus fraxineus, and the active principles were identified after preparative isolation and classical structure elucidation (NMR spectroscopy and HR mass spectrometry) as phomopsidin derivatives [123,124]. In a follow-up study, the production of phomopsidins (85)(86) in presence of the pathogen was observed in various strains of species that are phylogenetically related to H. rubiginosum including the new species, H. guilanense, but not in some distantly related species like H. fuscum.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%